2018
DOI: 10.1038/s41428-018-0130-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carboxylated derivatives of poly(isobutylene-co-isoprene) by azide–alkyne “click” chemistry

Abstract: The synthesis of carboxylated derivatives of poly(isobutylene-co-isoprene) (isobutylene-isoprene rubber, IIR) with substitution levels ranging from 1-4 mol% and different spacer lengths was accomplished by azide-alkyne Huisgen cycloaddition. Azido-functionalized IIR was first prepared by reacting brominated IIR to full conversion with sodium azide in a tetrahydrofuran/N,Ndimethylacetamide 90:10 mixture. The click reaction of the azido-functionalized IIR with acetylenic acids, using the copper(I) bromide/N,N,N′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Butyl rubber is prepared by the cationic copolymerization of isobutylene and isoprene (0.5–2.5 mol %). The incorporation of isoprene units provides butyl rubber with unsaturation, which allows for vulcanization and further postpolymerization functionalization. Despite the low unsaturation as compared to other synthetic rubbers such as butadiene rubber (BR), butyl rubber is widely used as an innerliner in tires and for pharmaceutical stoppers owing to its exceptional impermeability to gas resulting from the densely packed polymeric chains. , Meanwhile, in rubber compounding, fillers such as carbon black, clay, and silica are often added to reduce the cost and improve the physical properties of rubber compounds . The dispersion of fillers in a rubber compound plays an important role in the performance of a rubber product. , However, because of the nonpolar nature of butyl rubber, the dispersion of fillers, especially polar fillers such as silica, into the butyl rubber matrix is difficult .…”
Section: Introductionmentioning
confidence: 99%
“…Butyl rubber is prepared by the cationic copolymerization of isobutylene and isoprene (0.5–2.5 mol %). The incorporation of isoprene units provides butyl rubber with unsaturation, which allows for vulcanization and further postpolymerization functionalization. Despite the low unsaturation as compared to other synthetic rubbers such as butadiene rubber (BR), butyl rubber is widely used as an innerliner in tires and for pharmaceutical stoppers owing to its exceptional impermeability to gas resulting from the densely packed polymeric chains. , Meanwhile, in rubber compounding, fillers such as carbon black, clay, and silica are often added to reduce the cost and improve the physical properties of rubber compounds . The dispersion of fillers in a rubber compound plays an important role in the performance of a rubber product. , However, because of the nonpolar nature of butyl rubber, the dispersion of fillers, especially polar fillers such as silica, into the butyl rubber matrix is difficult .…”
Section: Introductionmentioning
confidence: 99%
“…Platform chemicals, defined as essential chemical building blocks serving as precursors to numerous secondary chemicals and materials are essential components of our economy. Ethylene and isoprene are platform chemicals with conjugated double bonds and the primary substrates for the production of many polymers such as synthetic rubber and resins (Easterbrook and Allen, 1987;Deepak et al, 2019). With the advance of industrialization, the demand for basic industrial materials is rising.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9][10][11] The solution-borne IIR derivatives bearing reactive functionalities, such as carboxyl group, ester group and ether group, were prepared by nucleophile substitution of BIIR. 3,11,12 With respect to pyridine or imidazole nucleophile substitution of BIIR, the structure and chain length of the nucleophiles, and the substitution sited on the heterocyclic ring affect the structure and properties of the ionic clusters, which subsequently influence the mechanical properties and self-healing efficiency of the ionic-modified elastomers. 13,14 Previous studies have shown that the introduction of pyridine derivatives tethered with -H, -CH 3 and -C(CH 3 ) 3 onto the fourth carbon of the pyridine ring increases the interaction between pyridyl cations and bromine anions and gives rise to a conversion ratio in excess of 70% due to the electron-donating effect.…”
Section: Introductionmentioning
confidence: 99%